Determination of Optimum Point of Composition of Fuel Calories in Producing electrical Energy in Coal Fired Power Plant - Jonathan Dian; Wahyu Wibowo (Institut Teknologi Sepuluh Nopember, 2020)
Coal-fired power plant (CFPP) is a type of power plant that is widely used for 35,000 MW electricity projects in Indonesia. CFPP must adjust to its operating strategies with the availability of abundant low-rank coal, and it will affect CFPP performance. This study aims to determine the optimum heating value of fuels, the trend of net plant heat rate (NPHR), the cost of electricity production (component C), and the optimum point of the CFPP operation. The data used is from CFPP operations. First, data is analyzed by descriptive statistics and formed into a regression model. The next step is to estimate the parameters of the population data. The regression model obtained was then carried out the goodness of fit test and residual analysis. Then, the variable’s values are changed to the Z-score and plotted in the regression model. The model interpretation is carried out and conclusions can be obtained to find out the optimum point. The conclusion of this study is the optimum point of generating electricity in CFPP can be achieved by using coal calorific values of 4,450 kCal/kg, NPHR of 2,683.6 kCal/kWh, and COE (component C) of Rp 436.5/kWh when using coal at a price of 732.2/kg and Net Power of 279 MW.